Increasing the Creative Economy through Utilization of Fruit Wrapping Waste and Food Bags as Decorative Flowers Crafts in Langon, Ambulu District of Jember Regency - Reni Umilasari; Ilanka Cahya Dewi (OJS Universitas Muhammadiyah Gresik, 2021)
The Covid-19 pandemic causes the number of unemployed to increase in 2020. The National Development Planning Agency (Bappenas) stated that the unemployment rate is expected to increase by 4 million to 5.5 million in 2020 and around 7.7 percent to 9.1 percent in 2021. This of course has an impact on the economic condition and welfare of the community. One of the efforts that can be made to prevent and reduce the unemployment rate is by creating new jobs, so that efforts to increase the creative economy must always be carried out to support the formation of new jobs. Increasing the quality of human resources, efforts to increase the creative economy can be done. In this Stimulus Community Partnership Program (PKMSS) activity, a concrete manifestation of increasing skills and knowledge can be done by providing training on making decorative flowers made from fruit wrapping / sarong waste and food bags to PKK RT 003 RW 030 women in Langon Hamlet, Ambulu Village District Ambulu. In addition, marketing activities through social media or market places will also be given special training. The objectives of this PKMSS activity include: (1) Increasing the knowledge and skills of the community in waste management that are commonly encountered on a daily basis; (2) reducing the amount of waste for fruit wrappers and food bags; (3) Creating new business opportunities, especially for PKK RT 003 RW 030 women in Langon Hamlet, Ambulu District. Quoting data from CupoNation Indonesia, domestic e-commerce platforms still control the number of website visitors throughout 2019 even though several international online shopping sites are also included in the ranks of the e-commerce market in Indonesia. Therefore, digital-based marketing training through social media or e-commerce needs to be given to expand product marketing.